1988
DOI: 10.1089/jir.1988.8.393
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NK Cells in Subjects Exposed to Mild Hyper- or Hypothermic Load

Abstract: The effect of mild hyper- and hypothermic stress on release of selected hormones (somatotropin, noradrenaline, etc.), interferon (IFN), and activity of NK cells in the blood was examined in groups of young males during a 30 min exposure to 39 degrees C and 4 degrees C. A quick release of somatotropin was registered in 44% of examinees in the hyperthermic group, while the persons exposed to 4 degrees C reacted with a release of noradrenaline only. Concurrently, an elevation of NK cell activity was observed both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Moderate cooling (in vivo studies) increases natural killer cell activity (11,34), white blood cell counts, (24) and monocytic expression of IL-6 and TNF-␣ (11) in human subjects. In vitro studies using human cell lines incubated at 32°C and 33°C showed increased IL-10 and decreased interferon gamma cytokine gene expression in peripheral blood cultures (49), decreased production of IL-10 in peripheral mononuclear blood cells (41), and prolonged activation of nuclear factor B and increased proinflammatory cytokine gene expression in LPS- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate cooling (in vivo studies) increases natural killer cell activity (11,34), white blood cell counts, (24) and monocytic expression of IL-6 and TNF-␣ (11) in human subjects. In vitro studies using human cell lines incubated at 32°C and 33°C showed increased IL-10 and decreased interferon gamma cytokine gene expression in peripheral blood cultures (49), decreased production of IL-10 in peripheral mononuclear blood cells (41), and prolonged activation of nuclear factor B and increased proinflammatory cytokine gene expression in LPS- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Icv injection of losartan decreases levels of resting renal SND in rats with chronic heart failure (11), and chronic central AT 1 receptor blockade normalizes the enhanced sympathoexcitation, reduced sympathoinhibition, and desensitized baroreflex responses observed in congestive heart failure rats after myocardial infarction (56). Congestive heart failure patients exhibit clinical features that are observed in chronic inflammatory conditions (10,34,50). For example, plasma levels of proinflammatory cytokines, notably IL-6 and TNF-alpha, are elevated in congestive heart failure patients and serum levels of IL-10, a potent anti-inflammatory cytokine, are reduced (10,34,50).…”
Section: Real-time Rt-pcr Analysis Of Splenic Gene Expression Responsmentioning
confidence: 99%
“…Congestive heart failure patients exhibit clinical features that are observed in chronic inflammatory conditions (10,34,50). For example, plasma levels of proinflammatory cytokines, notably IL-6 and TNF-alpha, are elevated in congestive heart failure patients and serum levels of IL-10, a potent anti-inflammatory cytokine, are reduced (10,34,50).…”
Section: Real-time Rt-pcr Analysis Of Splenic Gene Expression Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a brief bout (30 min) of cold (4°C) air exposure increases NK cell activity (60). We thus hypothesized that exposure to cold air (5°C) for 2 h would have immunostimulating effects and that pre-treatment with exercise or passive heating would have algebraically additive effects on this response.…”
Section: Immersion Of Healthy Young Men In Cold (14°c) Water Induces mentioning
confidence: 99%